2022
DOI: 10.3390/plants11151913
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Effect of Triacontanol in Combating Drought Stress by Improving Growth, Productivity, and Physiological Performance in Strawberry Plants

Abstract: To explore the effects of triacontanol (TR) on drought tolerance of strawberry plants (cv Fertona), two field experiments were carried out to study the effects of three supplementary foliar TR rates (0, 0.5, and 1 ppm) under the following three levels of water irrigation: 11 m3/hectare (40% of water holding capacity (WHC) severe as a drought treatment, 22 m3/hectare (80% of WHC) as moderate drought stress, and normal irrigation with 27 m3/hectare (100% of WHC) server as a control treatment. TR treatments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…As a result, plants with stronger root systems establish themselves more quickly. Organic mulches promote root development more than bare soil [262][263][264][265].…”
Section: Strategies For Optimum Water Usage In Urban Green Spaces And...mentioning
confidence: 99%
“…As a result, plants with stronger root systems establish themselves more quickly. Organic mulches promote root development more than bare soil [262][263][264][265].…”
Section: Strategies For Optimum Water Usage In Urban Green Spaces And...mentioning
confidence: 99%
“…Four compounds were detected at all levels of drought stress treatment such as triacontanal, dl-αtocopherol, 1-tricosane, dan 2,5-dihydroxybenzoic acid. Triacontanal reduces the effects of drought stress by increasing antioxidant enzymes, photosynthetic rates, and water use efficiency in leaves [12]. dl-α-tocopherol increases antioxidant enzymes and proline accumulation [13].…”
Section: Discussionmentioning
confidence: 99%
“…Physiological effects have been related at the biochemical level to a cellular increase in the content of photosynthetic pigments, soluble sugars, starch, phenols, and proteins 5 , and to stimulation of the activities of carbon and nitrogen metabolism enzymes, such as carbonic anhydrase 5 , 6 , nitrate reductase 6 , ribulose-1,5-bisphosphate carboxylase/oxygenase 7 , and respiratory malate dehydrogenase 8 . More recent studies documented that triacontanol improves the tolerance of plants to abiotic stresses, including salinity 9 , 10 , drought 11 , temperature 12 , and heavy metals 13 , 14 . In general, these studies demonstrated that the improvement of tolerance to stress is due primarily to the increase in the activities of antioxidant enzymes, such as superoxide dismutase, catalase, peroxidase, and those involved in the ascorbate–glutathione cycle 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In general, these studies demonstrated that the improvement of tolerance to stress is due primarily to the increase in the activities of antioxidant enzymes, such as superoxide dismutase, catalase, peroxidase, and those involved in the ascorbate–glutathione cycle 14 . The increase in antioxidant enzyme activity contrasts the oxidative damage, a common feature of various abiotic stresses 11 , thereby resulting in the mitigation of cell injury and the restoration of plant growth.…”
Section: Introductionmentioning
confidence: 99%